Peran Dinas Kehutanan Dalam Menanggulangi Tindak Pidana Illegal Logging diKelurahan Umanen, Kecamatan Atambua Barat, Kabupaten Belu - Eduardus Franko Sufani; Heryanto Amalo; Bhisa Vitus Wilhelmus (Artemis Law Journal, 2026)
The problem of illegal logging is actually a very complex matter, because it is not only related to the law enforcement or juridical aspects, but also related to economic, sociological and cultural aspects. This illegal logging practice is generally carried out by individuals who actually have official permits from the Indonesian government to carry out logging on land, such as holders of Forest Concession Rights (HPH) concession permits. The type of research in this study is empirical legal research. The types and sources of data used are primary data and secondary data. The role of the Forestry Service in overcoming illegal logging practices in the Umanen area, West Atambua District, Belu Regency is carried out with two handling approaches, namely the preventive approach, namely the approach to the community, empowering the community, and reforestation (replanting bare forests). The repressive approach, namely conducting operations, and imposing severe sanctions on those who violate. Obstacles in overcoming Illegal Logging include legal obstacles, geographical factors, lack of law enforcement facilities and infrastructure, weak coordination between law enforcers, and community human resource factors.